Kustomisasi Pengembangan Kompetensi Melalui Model Manajemen Analisis Kebutuhan Pengembangan Kompetensi bagi Pegawai Negeri Sipil di Wilayah Kerja Binaan PPSDM Kemendagri Regional Bandung - Sudrajat (Jurnal Kesehatan & Disiplin Ilmu, 2024)
Competency Development Planning is a bill for private employees and government organizations today. The purpose of this study is to obtain a model that meets the requirements in analyzing competency development needs. The method of this research is qualitative Research and Development (R&D) which is equipped with the SOAR (Strengths, Opportunities, Aspirations, and Results) analysis method. Data collection was carried out through: (1) documentation studies sourced from (a) research result documents published in journals related to competency development research and (b) competency development documents at competency development organizing institutions using activity implementation checklist sheets; and competency development documents using activity implementation checklist sheets; and (2) opinion polls using questionnaires related to the actual condition of employee competency. The data analysis technique uses simple descriptive statistics and qualitative analysis in the form of a Systematic Literature Review (SLR). The results of the analysis, synthesis, and recommend 3 (three) major stages of the Competency Development Needs Analysis (AKPK) business process: (1) Preparation of AKPK Facilitators which is carried out through AKPK facilitator training (Training of Facilitators); (2) Analysis of Competency Development Needs which is carried out in several stages and steps accompanied by a number of forms to be filled in and inputted into the AKPK information system (SI-AKPK).